Ethnolinguistic vitality of the Malays of Singapore / Mohamed Pitchay Gani bin Mohamed Abdul Aziz - Mohamed Abdul Aziz, Mohamed Pitchay Gani (2014)
This thesis describes the ethnolinguistic vitality of the indigenous Malays of Singapore forty-five years after Singapore’s separation from Malaysia. The study sets out to explore the vitality of the Malay language in Singapore and the factors that influence it. It also seeks to know whether the Malay language has really come to a deficit in Singapore, in terms of language use. The general literature on this subject shows that sociolinguistic researches in Singapore are more focused on socio-psychological framework, especially when dealing with the Malay language-use situation. Such approach lacks the sociological framework that together would provide a holistic look at the issue of language use. The need for sociological approach becomes more apparent with the Singapore government’s interventionist stance in language planning and demographic engineering, because sociological factors condition the individual’s socio-psychological and interactional climate, apart from playing decisive role in the survival of a language. Hence, this study embarks on a macro-sociolinguistic research to determine the influence or effect of social factors on individual language use and attitude. The data is derived from a total of 2435 youths in the form of questionnaire survey and interviews. This study has benefited from Giles, Bourhis, and Taylor (1977)’s Ethnolinguistic Vitality (EV) framework that provides the sociological factors needed to evaluate the position of the Malay minority against the dominant Chinese and the hegemony of the English language in Singapore. The factors have provided the elements needed to generate detailed descriptions of the intergroup situation that help to explain what makes the Malays behave as a distinctive and active collective entity in intergroup situations. The overall finding from EV theory subscribes to the notion of the hypothetical question of whether the Malay language has come to a deficit. It shows that Malay vitality is in the low to medium range, which translates into a situation towards language deficit. Malay relies more on ethnolinguistic affiliations rather than government support. The geographic and informal institutional support factors are identified as significant in generating the vitality despite the weak status and low demographic position of the Malays. This proves that EV theory is able to accurately assess the sociological situation and perceptions of a group and its language position in an intergroup situation. However, socio-psychological data from the use of surveys, interviews, and personal observations in this study has provided consistent findings on the overall vitality of Malay in Singapore. The actual language use situation shows high vitality. The individual’s language use vitality is high and is motivated by home, school, friends and religion that create the necessary environments to instil the identity, loyalty, and attachment to the language. Out of this all, home and religion play the most significant roles in nurturing language use while school and friends provide the linguistic (standard use of language) and sociolinguistic (variations in colloquial usage) support respectively. This means that the EV theory has to be complemented with other conceptual tools to generate a more accurate interpretation of language vitality because sociological factors alone may only generate superficial outcomes. This study concludes that Malays are able to differentiate the role of English and Malay and to use the languages based on context and needs. English is preferred for education and jobs while Malay continues to be cherished as a marker of ethnicity. Hence, Malays’ ability to make pragmatic choices when it comes to language use helps to maintain a healthy vitality for Malay in Singapore.